Nicaragua - Responding to the Needs of Farmers Using Agricultural Technology, Knowledge and Innovation Systems - Piccioni, Norman Bentley (World Bank, Washington, DC, 2012)
The Nicaraguan agricultural and livestock sector experienced wide policy shifts over the last two decades. State intervention during the Sandinista period (1979--1990) was reversed by subsequent governments that drastically reduced credit, curtailed government technical assistance services, and liberalized foreign and domestic input and output markets. However, government withdrawal was not accompanied by promotion of institutions to facilitate competition in input and output markets, and/or provision of credit and technical assistance.